Asymptotic analysis on steady-state response of axially accelerating beam constituted by the standard linear solid model - Wang, B.; Qiu, J. (Прикладная механика, 2017)
The transverse bending vibrations of an axially accelerating viscoelastic beam are studied. A material of beam is constituted by the standard viscoelastic model. The method of multiple scales is applied to determine the steady-state response of beam. The numerical examples illustrate the asymptotic solution. Вивчено поперечні згинні коливання в'язкопружної балки, яка допускає рухи вздовж осі. Матеріал балки припускається деформівним за стандартною триконстантною моделлю теорії в'язкопружності. Для визначення стаціонарної реакції балки застосовано метод багатьох масштабів. Числові приклади ілюструють асимптотичний розв'язок.